SENYAWA METABOLIT SEKUNDER EKSTRAK METANOL DAUN MANGROVE SONNERATIA ALBA DAN SIFAT TOKSISITASNYA - Indri Rizki Eriani; Usman Usman (PROSIDING SEMINAR KIMIA, 2017)
Sonneratia alba is one of the most important and widespread mangrove species. Although Indonesia has various types of mangroves but the utilization of mangroves as medicinal products, food and health has not been done because of the limited information about bioactive compounds in mangroves. The aim of this research is to know phytochemical group contained in mangrove leaf extract of Sonneratia alba and toxicity content of mango leaf extract of Sonneratia alba to Artemia salina larvae. Phytochemical tests performed are alkaloids, flavonoids, steroids / triterpenoids, saponins, phenolic and tannins. The method used in the toxicity test against Artemia salina is the BSLT method of this method carried out in the preliminary test for screening or screening pharmacological activity on natural products. The results showed that mango leaf extract of Sonneratia alba contain phenol, steroid / triterpenoid, saponin and tannin. Based on the results of toxicity test of mango leaf extract of Sonneratia alba has weak toxicity because obtained LC50 result more than 100 μg / mL that is 441.67 ppm. So that can be done further testing anti-cancer activity and drug development. Keywords: Sonneratia alba, phytochemicals, toxicity, Artemia salina